2016
DOI: 10.18632/oncotarget.9812
|View full text |Cite
|
Sign up to set email alerts
|

A novelCBL-Bflox/floxmouse model allows tissue-selective fully conditionalCBL/CBL-Bdouble-knockout: CD4-Cre mediatedCBL/CBL-Bdeletion occurs in both T-cells and hematopoietic stem cells

Abstract: CBL-family ubiquitin ligases are critical negative regulators of tyrosine kinase signaling, with a clear redundancy between CBL and CBL-B evident in the immune cell and hematopoietic stem cell studies. Since CBL and CBL-B are negative regulators of immune cell activation, elimination of their function to boost immune cell activities could be beneficial in tumor immunotherapy. However, mutations of CBL are associated with human leukemias, pointing to tumor suppressor roles of CBL proteins; hence, it is critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…In view of reduced MG development and of MaSC depletion upon Cbl/Cbl-b DKO, we assessed whether AKT-mTOR signaling is hyperactivated in DKO MECs. As the number of cells available from the Lgr5-Cre-driven model was small, we used a fully tamoxifen-inducible Cbl and Cbl-b deletion model (Goetz et al, 2016) in which both Cbl and Cbl-b are floxed, and the ROSA26 locus CreERT and dual fluorescent reporter (mT/mG) alleles allow verifiable 4-OH-T-inducible in vitro Cbl and Cbl-b deletion. The MaSC-containing basal cells from Cbl f/f ; Cbl-b f/f ; CreERT; mT/mG or Cbl f/f ; Cbl-b f/+ ; CreERT; mT/mG mice were plated in organoid cultures and induced with 4-OH-T (Fig.…”
Section: Mmtv-cre-mediated Cbl Deletion On a Cbl-b Null Background (Cmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of reduced MG development and of MaSC depletion upon Cbl/Cbl-b DKO, we assessed whether AKT-mTOR signaling is hyperactivated in DKO MECs. As the number of cells available from the Lgr5-Cre-driven model was small, we used a fully tamoxifen-inducible Cbl and Cbl-b deletion model (Goetz et al, 2016) in which both Cbl and Cbl-b are floxed, and the ROSA26 locus CreERT and dual fluorescent reporter (mT/mG) alleles allow verifiable 4-OH-T-inducible in vitro Cbl and Cbl-b deletion. The MaSC-containing basal cells from Cbl f/f ; Cbl-b f/f ; CreERT; mT/mG or Cbl f/f ; Cbl-b f/+ ; CreERT; mT/mG mice were plated in organoid cultures and induced with 4-OH-T (Fig.…”
Section: Mmtv-cre-mediated Cbl Deletion On a Cbl-b Null Background (Cmentioning
confidence: 99%
“…ROSA26 locus lacZ reporter [B6.129S4-Gt(ROSA)26Sor tm1Sor/J ] and EGFP reporter (CAG-CAT-EGFP) (Naramura et al, 2010) ; CreERT; mT/mG strain that was used for in vitro Cbl and Cbl-b deletion in MaSCs in certain experiments (Goetz et al, 2016). Three-week-old female NSG mice (NOD.Cg-Prkdc scid Il2rg tm1Wjl/SzJ ) (The Jackson Laboratory) were used as recipients for mammary transplantation.…”
Section: Mouse Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice, cell lines, and primary human samples Cbl f/f ;Cbl-b f/f mice were generated as described (Goetz et al 2016) and crossed to cre ERT2 mice from Jackson Laboratories. Lnk −/− mice were generously provided by Dr. Tony Pawson and Dr. Laura Velazquez (Samuel Lunenfeld Research Institute, Toronto, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…−/− and conditional Cbl) develop an aggressive CMML-like MPN due to an unexpected Cre activation in a fraction of HSCs (Naramura et al 2010). We recently generated conditional doubleknockout alleles for both Cbl and Cbl-b (Cbl f/f ;Cbl-b f/f ) (Goetz et al 2016), which show normal survival in the uninduced state. We found that pan-hematopoietic Vavcre-mediated deletion causes early lethality (day 10), preventing us from studying adult hematopoiesis .…”
Section: Cbl Depletion or Inactivation Enhances Jak2 Signalingmentioning
confidence: 99%